Reproducción de Mycteroperca bonaci y Mycteroperca venenosa (Pisces: Serranidae) en la plataforma cubana - García-Cagide, Alida; García, Tsai (Revista de Biología Tropical, 1996)
Reproductive characteristics of the black grouper Mycteroperca bonaci and the yellow-fin grouper M. venenosa were studied off Cuba. Both species are protogynous, hermaphroditic, and monandric. All individuals of both species change sex usually around 65 cm of total lenght CL T) and after spawning as females at least once. The sex ratios were 30.3 females per male in black groupers and 9.3: 1 in yellow-fin groupers. Ripe females of both species had a size range of 55-60 cm LT. The smallest size in ripe males of M. bonaci was 98 cm LT (71 cm in M. venenosa). The condition factor during ontogeny increases with gonadal development. Both species spawm during winter and spring. Vitelogenesis is asynchronic and spawning is portional in both species. Gonadosomatic index in ripe fishes varied from 0.85 lo 4.96 in females and from 1.44 lo 6.80 in males.